Measuring Systems Engineering Transformation: A systematic literature review - Gräßler, Iris; Grewe, Benedikt
Established companies are undertaking major transformation initiatives of their corporate structures and organisational forms to cope with the complexity during the engineering of cyber-physical production systems (CPPS). A frequently discussed issue is the measurability of this transformation progress. This paper conducts a systematic literature analysis of approaches regarding measurability of transformation and evaluates their application in the context of a systems engineering transformation. Measure-ment criteria are derived from the identified approaches, categorised, and finally evaluated by industry experts regarding their applicability. The categorised measurement criteria can be used to accurately measure the progress of a transformation process.
Keywords: Organizational Transformation; Systems Engineering; Meausrement; Metrics; Organizational Change

The importance of structure in transformation chaos: A Transformation Framework - Gräßler, Iris; Grewe, Benedikt; Fritzen, Marc (AHFE International)
Dynamic market conditions, technological disruption and social change require organizations to continuously adapt and evolve. However, studies on organizational change show that the majority of transformations undertaken fail because they are characterized by a lack of clarity, overload and ineffective measures. This paper shows how a clear structure as a critical success factor can make the chaos and challenges of a transformation manageable. The focus here is on a practice-oriented framework that divides a transformation into nine essential building blocks with activities that are critical to success. The structure of the framework is understood as a flexible organizing principle for a transformation without hindering creativity and dynamics. Case studies show the adaptability and applicability of the framework to different characteristics and dimensions of transformation. The transformation framework provides an operative structure and enables transformation managers for transparent orchestration and implementation of transformation.

Strategic Product Planning Model – Digital twins for circular products and production processes - Gräßler, Iris; Rarbach, Sven; Grewe, Benedikt (Industry 4.0 Science)

Structuring Systems Engineering Transformation: A three-step cycle of Transformation - Gräßler, Iris; Grewe, Benedikt (Procedia CIRP)

Evolving Design for Assembly, Disassembly and Reassembly into a new paradigm: Design-for-Capabilities with Hybrid Decision Support as an enabler for circular products - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Schmidt, Matthias; Grewe, Benedikt; Vollenkemper, Felix; Hesse, Thomas; Meinecke, Tim (Stuttgarter Symposium für Produktentwicklung (SSP) 2025)

Stages of Systems Engineering: An Analysis and Characterization of Systems Engineering Approaches - Gräßler, Iris; Grewe, Benedikt (Systems)
In the engineering of complex technical systems, Systems Engineering (SE) is a key approach that is becoming increasingly relevant in more and more industries due to the ever-increasing complexity of systems. Over the decades of practical application and research, various specializations and forms of the Systems Engineering approach have developed, but there has so far been a lack of an overarching context and positioning in meaningful stages for the introduction of Systems Engineering in companies. For this reason, this research will systematize common Systems Engineering approaches and bring them together in a stage model for Systems Engineering. Based on a systematic literature review, use cases are identified for each approach and stage, which support companies in selecting an approach suitable for their own organization.
Keywords: Systems Engineering Transformation; maturity; Systems Engineering stages; approaches; SE

Forschen für die Zukunft der Produktentstehung. Innovation erleben und validieren - Gräßler, Iris; Pottebaum, Jens; Grewe, Benedikt (VDI Konstruktion)

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Literature study on the potential of Artificial Intelligence in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie; Thiele, Henrik; Preuß, Daniel; Grewe, Benedikt; Hieb, Michael (XXXIII ISPIM Innovation Conference Proceedings)

Supporting Business Model Generation with Augmented Reality - Gräßler, Iris; Grewe, Benedikt; Kramer, Hendrik; Pottebaum, Jens (LUT Scientific and Expertise Publications)
Workshops on business model generation lead to collaborative work phases and discussions on business models. Therefore, tools such as the Business Model Canvas are used, typically filled with sticky notes. Generated content needs to be digitized in a time-consuming manual follow-up as part of the documentation and basis for a further use of the results in the company. In addition, there are challenges, such as decentralized work and digital workshop formats. Augmented Reality offers a way to reduce the digitization effort and enables decentralized work. In this research, the potentials of the use of AR technology in workshops on business model generation is investigated. Therefore, functions are implemented and evaluated in a demonstrator that reduces digitization effort and enable distributed work.
Keywords: business model generation; augmented reality; workshop; collaborative work; digitization; AR-supported workshop concept; immersive technologies; decentralized work; business model canvas